2021
DOI: 10.3390/pathogens10040395
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Inhibitors Differently Affect Toxoplasma gondii, Neospora caninum and Besnoitia besnoiti Proliferation in Bovine Primary Endothelial Cells

Abstract: Apicomplexan parasites are obligatory intracellular protozoa. In the case of Toxoplasma gondii, Neospora caninum or Besnoitia besnoiti, to ensure proper tachyzoite production, they need nutrients and cell building blocks. However, apicomplexans are auxotrophic for cholesterol, which is required for membrane biosynthesis. P-glycoprotein (P-gp) is a transmembrane transporter involved in xenobiotic efflux. However, the physiological role of P-gp in cholesterol metabolism is unclear. Here, we analyzed its impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…These findings are in line with the function of SR-BI in endothelial cell cholesterol efflux [27], being a consequence of SR-BI blockage, thereby impairing its capacity for HDL-dependent cholesterol efflux and finally resulting in cellular neutral lipid accumulation [52]. Interestingly, we recently reported that verapamil treatments also reduced T. gondii-, N. caninumand B. besnoiti tachyzoite replication, which was accompanied by enhanced neutral lipid accumulation [15]. It seems, therefore, plausible to speculate that cholesterol efflux impairment may generally affect obligate intracellular coccidian development.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…These findings are in line with the function of SR-BI in endothelial cell cholesterol efflux [27], being a consequence of SR-BI blockage, thereby impairing its capacity for HDL-dependent cholesterol efflux and finally resulting in cellular neutral lipid accumulation [52]. Interestingly, we recently reported that verapamil treatments also reduced T. gondii-, N. caninumand B. besnoiti tachyzoite replication, which was accompanied by enhanced neutral lipid accumulation [15]. It seems, therefore, plausible to speculate that cholesterol efflux impairment may generally affect obligate intracellular coccidian development.…”
Section: Discussionsupporting
confidence: 72%
“…For LD visualization, BUVEC were seeded into 35 mm tissue culture µ-dishes (Ibidi ® ) and treated with the vehicle and BLT-1 for 48 h as described above. Then, the treated cells were loaded with BODIPY 493/503 (2 µg/mL, 1 h, 37 • C, 5% CO 2 ; Cayman Chemical, Ann Arbor, MI, USA) as described elsewhere [15]. Cellular LDs in the BLT-1-treated cells and non-treated controls (n = 50 per condition) were manually counted based on morphology and BODIPY 493/503-driven signal accumulation in endothelial cells [39] and expressed as the number of LDs per cell.…”
Section: Live Cell 3d Holotomographic Microscopy and Lipid Droplet (Ld) Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, the host cells survive and support this development by an intense cytoskeletal re-organization (Hermosilla et al, 2008). Full macromeront formation takes up to 25 days and thereby considerably exceeds the merogonies of other closely related apicomplexans, such as T. gondii, Neospora caninum, or B. besnoiti (Conejeros et al, 2019;Velaśquez et al, 2019;Velaśquez et al, 2020a;Velaśquez et al, 2020b;Larrazabal et al, 2021). Besides cytoskeleton, E. bovis modulates several pathways and cellular functions, such as apoptosis, cholesterol biosynthesis, immune responses, or cell cycle progression to complete its intracellular development (Lang et al, 2009;Hamid et al, 2015;Velaśquez et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%